ANALISIS BUSINESS LEVEL STRATEGY DAN DIVERSIFICATION PERUSAHAAN SAMSUNG - Adi Wilyanto; Angelina Julia Renaldi; Eni Valentina; Richmond Richmond; Rieza Melinda; Adi Neka Fatyandri (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The writing of the article